2021
DOI: 10.3390/vaccines9080863
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to COVID-19 Vaccination and Reasons for Hesitancy in Employees of a Czech Tertiary Care Hospital: A Cross-Sectional Survey

Abstract: High vaccination coverage among healthcare workers (HCWs) is crucial for managing the COVID-19 pandemic. The aim was to determine the demand for vaccination among all employees (n = 4553) of a tertiary care hospital after several weeks of the vaccine’s availability, and to analyze motives for acceptance and reasons for hesitancy through an anonymous online questionnaire. Upon the completion of data collection, the hospital’s vaccination coverage was at 69.8%. A total of 3550 completed questionnaires were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
52
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 22 publications
4
52
3
Order By: Relevance
“…A study by Raftopoulos et al, amongst 2238 Greek and Cypriot HCWs, revealed the same order of the strongest motives as in the HCWs from our study, i.e., family protection being the primary motive (98.7%), followed by patient (95.2%) and self-protection (94.2%) [ 13 ]. The same order of vaccination motives was also found in a recent study among already vaccinated employees of UHO [ 9 ].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…A study by Raftopoulos et al, amongst 2238 Greek and Cypriot HCWs, revealed the same order of the strongest motives as in the HCWs from our study, i.e., family protection being the primary motive (98.7%), followed by patient (95.2%) and self-protection (94.2%) [ 13 ]. The same order of vaccination motives was also found in a recent study among already vaccinated employees of UHO [ 9 ].…”
Section: Discussionsupporting
confidence: 81%
“…They also wished to contribute to the further easing of restrictions (80%), enable social contact (75%), and to have more travel opportunities (70%) [ 17 ]. This means that, as in the present study and the cited recent study among employees of UHO [ 9 ], all of which analyzed the situation of already vaccinated individuals, motives that aimed to protect others were dominant. With regards to the top reasons for COVID-19 vaccination hesitancy in HCWs, the majority of studies found concerns about vaccine safety, efficacy, and potential side effects [ 18 ].…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…A Microsoft Forms questionnaire was used, which was adopted from Stepanek et al with their consent [ 11 ]. Socio-demographic characteristics were collected among all respondents.…”
Section: Methodsmentioning
confidence: 99%